The role of bafilomycin as a therapeutic agent in the modulation of endo-lysosomal store of rat hepatocytes - S.V. Bychkova; A.R. Stasyshyn; M.A. Bychkov (Medičnì Perspektivi)
Endo-lysosomal system through the process of autophagy is involved in the pathogenesis of many diseases. Acidification of these organelles is carried out by V-type H+-ATPases, which is inhibited by bafilomycin A1. Endosomes and lysosomes are also important Ca2+-storage in a cell. Nіcotіnіc acіd adenіne dіnucleotіde phosphate (NAADP) releases Cа2+ from endo-lysosomes. The main purpose of the study was to found out the effect of bafilomycin A1 and NAADP on stored Ca2+ and on the ATPase activity of rat hepatocytes. The stored Ca2+ was estimated using chlorotetracycline in permeabilized hepatocytes of rats. ATPase activity was determined by level of orthophosphate spectrophotometrically. It was found that bafilomycin A1 reduces stored Ca2+ in permeabilized hepatocytes of rats in the micromolar range of concentration (20 and 0.04 mkM) and averted the effect of NAADP on calcium content. Lower concentrations of bafilomycin A1 (0.001 mkM) did not alter the content of stored calcium, but prevented the influence of NAADP in permeabilized hepatocytes of rats. In the subcellular fraction of rat liver bafilomycin A1 (0.001 mkM) increased Ca2+-ATPase and  basal Mg2+-ATPase activities and reduced Na+/K+-ATPase activity. Preincubation of the subcellular fraction with bafilomycin A1 completely averts any changes in the activity of estimated ATPases by means of NAADP. It was concluded that the bafilomycin-sensitive store in hepatocytes of rats is NAADP-sensitive endo-lysosomal Ca2+-store. Using of bafilomycin A1 may be useful in treating autophagy-depended diseases.